Forest of struggle : moralities of remembrance in upland Cambodia - Zucker, Eve Monique (Southeast Asia--politics, meaning, memory., 2013)
In a village community in the highlands of Cambodia's southwest, people struggle to rebuild their lives after nearly thirty years of war and genocide. Recovery is a tenuous process as villagers attempt to shape a future while contending with the terrible rupture of the Pol Pot era. This book tracks the fragile progress of restoring the bonds of community in O'Thmaa and its environs, the site of a Khmer Rouge base and battlefield for nearly three decades between 1970 and 1998. The anthropologist author's ethnographic fieldwork (2001-2003, 2010) uncovers the experiences of the people of O'Thmaa in the early days of the revolution, when some villagers turned on each other with lethal results. She examines memories of violence and considers the means by which relatedness and moral order are re-established, comparing O'Thmaa with villages in a neighboring commune that suffered similar but not identical trauma. She argues that those differing experiences shape present ways of healing and making the future. Events had a devastating effect on the social and moral order at the time and continue to impair the remaking of sociality and civil society today, impacting villagers' responses to changes in recent years. More positively, the author persuasively illustrates how Cambodians employ Indigenous means to reconcile their painful memories of loss and devastation. This point is noteworthy given debates on recovery surrounding the Khmer Rouge Tribunal. This book offers a compelling case study that is relevant to readers interested in post-conflict recovery, social memory, the anthropology of morality and violence, and Cambodia studies.